Experimental study on self compacting concrete using light weight aggregate. (2022) - Elango, K.S.; Vivek, D.; Anandaraj, S.; Saravanakumar, R.; Sanfeer, J.; Saravanaganesh, S.
Abstract: The inherent properties in Self Compacting Concrete (SCC) makes very popular in recent decades. When compaction of concrete is very difficult due to placing condition or congested reinforcement, SCC plays major role where it compacts by its own. This study investigates the influence of Light Weight Aggregates (LWA) in Self Compacting Concrete (SCC). Various tests are done such as workability, mechanical, and durability properties were determined and the results are discussed. To explore the possibility of using diatomite aggregate an attempt has been made by partially replacing natural coarse aggregate by diatomite aggregate with 5%, 10%, 15% and 20%. The results exhibited that replacement of natural coarse aggregate with diatomite aggregate has 22%, 24%, 26%, 28% decrease in compressive strength with replacement percentage of 5%, 10%, 15%, 20%.